A Corpus Based Contrastive Analysis of Attitude Markers in News Articles about COVID-19 (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: This Paper Presents A Corpus-Based Contrastive Study Which Examines The Frequency And Use Of Attitude Markers In News Reports About Corona Virus Pandemic By Journalists From Both The British Newspaper (Independent) And The Emirati (Khaleej Times). The Attitude Markers Are Compared In Terms Of The Grammatical Forms In Which They Appear And Their Frequency Using “Antconc” Software Following The Blagojevic(2009) Framework Which Subdivides Attitude Markers Into Six Categories. The Results Show That Journalists From Different Cultural Backgrounds Use Approximately Similar Ways To Express Their Attitudes But With Slight Differences In Percentages Because Of Their Different Cultural Backgrounds. The Frequency Shows That The Ranking Of The Six Categories Is The Same; Adjectives Are The Most Used Category, Adverbs Then Nouns Of Specific Semantic Content And Then The Remaining Three Categories With Very Rare Usage. The Study Suggests Some Implications And Concludes With Recommendations For Future Research In Media Discourse Analysis.Keywords: Attitude Markers, News Articles, Contrastive Analysis, Newspapers’ Discourse, Discourse Analysis.